2017
DOI: 10.3390/ma10020193
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Welding Energy on the Microstructural and Mechanical Properties of Ultrasonic-Welded Copper Joints

Abstract: The effects of welding energy on the mechanical and microstructural characteristics of ultrasonic-welded pure copper plates were investigated. Complex dynamic recrystallization and grain growth occurred inside the weld zone during ultrasonic welding. At a low welding energy, a thin band of straight weld interfaces was observed and had an ultra-fine grain structure. With an increase in welding energy, the weld interface progressively changed from flat to sinusoidal, and eventually turned into a convoluted wavy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 26 publications
6
24
0
1
Order By: Relevance
“…This is likely due to the effect of higher temperatures that exceed the recrystallization temperature. Similar results were also reported in an USWed copper alloy [ 51 ]. Several other authors also observed the formation of fine grains near the faying surface during USW [ 15 , 32 , 33 ] and during friction stir welding (FSW) of aluminum alloys [ 50 , 52 , 53 , 54 , 55 , 56 ].…”
Section: Resultssupporting
confidence: 90%
“…This is likely due to the effect of higher temperatures that exceed the recrystallization temperature. Similar results were also reported in an USWed copper alloy [ 51 ]. Several other authors also observed the formation of fine grains near the faying surface during USW [ 15 , 32 , 33 ] and during friction stir welding (FSW) of aluminum alloys [ 50 , 52 , 53 , 54 , 55 , 56 ].…”
Section: Resultssupporting
confidence: 90%
“…The progressive shear and plastic deformation caused by the elevated high frequency vibratory energy produces metallurgical coalescence between the different parts [1]. This makes UW insensitive to the thermal conductivity of the materials, making it particularly suitable for joining similar and dissimilar non-ferrous metals as well as alloys based on copper, aluminum, and magnesium, among other metals [2,3,4]. On the other hand, UW also has applications in other fields such as battery pack assembly, electrical wire connection, and light alloy structure welding.…”
Section: Introductionmentioning
confidence: 99%
“…The MAG welding process is based on welding in shielded gas with a consumable electrode and consists of forming the spring between the consumable wire—underwire shape—and the piece. The welding process can be used in semi-mechanized, mechanized, automated or robotic versions with reverse polarity if the welding source has a rigid external feature [ 15 , 16 , 17 ]. The control of the electric arc is achieved by means of the self-regulating mechanism while maintaining a constant value of the wire feed in the molten bath.…”
Section: Methodsmentioning
confidence: 99%